Decentralization and democratic transition in Iraq from the grandson's rebellion and the Republic of Basra to the Sunni region - watut, Ali Jawad (Al-Adab Journal, 2015)
This paper focus on the role of the democratic transition or the process of democratization of political stir placed decentralization or local governance in Iraq (administrative was or political), on the contrary, which appears in established democracies where the political stability and administrative prominent feature which, in the case of communities transitional form ethnic and religious conflicts and sectarian center of gravity in the transition process.Although the issue of the management of the regions in Iraq has received ample fortune of political debate and the media and even popular, but did not find anything like the level of academic interest, is no longer possible to deal with it as a matter of secondary, they represent the essence of the democratization process in Iraq.It also constitutes the current crisis between the governments of the center and the region timing appropriate to put the issue of decentralization in Iraq on the table and debate, not because this time is the period of rumination historic conflict center and the region only, but it could be the stage of dismantling problematic old models of political culture, which dealt with the issue, and try to build Bradegmat) (new, as well as being the stage of growing public pressure, and the mobility of civilians increasingly in order to resolve the outstanding issues between certain cities complaining about injustice and between the center, and there are projects to try to claim the territory of sectarian (Sunni, this time)In order that, the present paper is trying to put the most important issues relating to the issue of decentralization, as follows: decentralization ... in concept and trading, and decentralization of the modern Iraqi state .. motives and requirements, and the problem of decentralization in the constitution, decentralization and democratic transition in Iraq, and the Kurdistan Region .. . challenges and prospects for the solution possible.